ASSESSMENT OF CARDIAC RISK FACTORS IN MEDICAL STUDENTS OF TEHRAN UNIVERSITY - "M. J. Mahmoudi; E. Nematipour; S. Moradmand; M. Gharouni; M. Mahmoudi; N. Rezaei; A.R. Ahmadv N. Karimi" (Acta Medica Iranica, 2004)
Prevention of coronary heart disease, mainly by reducing the levels of known risk factors in the population, remains a priority in public health. This cross-sectional study on randomly selected medical students during their internship was conducted from July 2001 to April 2002 in order to determine the prevalence of major coronary artery disease (CAD) risk factors. This survey was done by filling the questionnaire, measuring physical parameters, and taking a fasting blood sample. Two hundred and sixty four medical students were evaluated in this study (48 female, 216 male) with the mean age of 26.5 ± 2.8 years. The main risk factors in descending order of frequency were physical inactivity (43.5%), low high-density lipoprotein cholesterol (26.2%), family history of premature CAD (15.9%), smoking (10.3%), abdominal obesity (10.2%), high triglyceride level (5.3%), high blood pressure (3.4%), and high low-density lipoprotein cholesterol (1.5%). Also, 25% of married females were using oral contraceptives regularly. The number of risk factors per person was 2.2 on average (1.1 in females and 2.5 in males). Prevalence of CAD risk factors in this medical students’ population was unacceptably high. Additional studies should be done to gather more information and determine the need for preventive, educational or curative interventions.